The complexity of references to the temporarily suspended norms of international tax treaties - I. A. Khavanova (Правоприменение)
Subject. The article is devoted to the theoretical aspects of the use in the tax legislation of references to the tax treaties provisions, the effect of which was suspended by Decree of the President of Russia dated August 8, 2023 No. 585.The purpose of the study. The purpose of the article is to assess the consequences of the suspension of certain provisions of tax agreements by Decree of the President of Russia dated August 8, 2023 No. 585, as well as the effectiveness of the decisions taken on the introduction of compensatory tax regulation. The essence of this regulation consists in the provision from August 8, 2023 by the Russian tax agent to apply reduced tax rates or nontaxation when paying income, if such rules are provided for by tax treaties, the validity of which is partially suspended.Methodology. The preparation phase included the following research methods: formal-logical analysis, system-based analysis, description, juxtaposition, synthesis and summarizing.Conclusions. The article concludes that the absence of a suspension procedure in agreements on the avoidance of double taxation (if there are rules on denunciation) is not an unconditional reason to consider it unlawful (in plus stat minus). At the same time, suspension should not be prohibited by the treaty and cannot be incompatible with its object and purposes. With regard to the partial suspension of tax treaties, the content and structure of tax conventions based on the OECD and/or UN model tax conventions allows (subject to certain conditions) the divisibility of contractual provisions according to the criterion of the type of income to which the distributive rules apply. The compensatory legal mechanism laid down in amendments to the Tax Code of the Russian Federation, adopted by Federal Law No. 539-FZ of November 27, 2023, is complex in nature and is aimed at entities that were entitled to expect reduced rates or non-taxation in Russia as a source of income, but lost this opportunity due to the suspension of certain provisions of international treaties. A reference norm is a norm, the constructive feature of which is the algorithm for combining normative prescriptions (internal and external in relation to the reference norm). The reference in the Tax Code of the Russian Federation to the norms of Russian tax agreements is a unilateral legislative decision of a Contracting State (Russia), although implemented based on the provisions of an international treaty. The author concluded that tax legislation does not exclude the possibility of using legal structures of a reference nature that require reference to the norms of an international tax treaty, provided that these structures are formulated with a sufficient degree of clarity that allows taxable persons to conform their behavior to them.